2022
DOI: 10.3390/universe8050275
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radio Bursts Associated with In Situ Detected Energetic Electrons in Solar Cycles 23 and 24

Abstract: The first comprehensive analysis between the in situ detected solar energetic electrons (SEEs) from ACE/EPAM satellite and remotely observed radio signatures in solar cycles (SCs) 23 and 24 (1997–2019) is presented. The identified solar origin of the SEEs (in terms of solar flares, SFs, and coronal mass ejections, CMEs) is associated with solar radio emission of types II, III and IV, where possible. Occurrence rates are calculated as a function of the radio wavelength, from the low corona to the interplanetary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A detailed review on previous works can be found in Klein (2021b). Miteva, Samwel, and Zabunov (2022) reported for the first time on the association between SEEs 10 (Samwel and Miteva, 2021) and radio emissions. When starting with the list of in situ electrons, the association rate with m-IIs in SC 24 is in the range 12−28%, whereas with DH-IIs is 23−29%.…”
Section: • In Situ Particlesmentioning
confidence: 99%
“…A detailed review on previous works can be found in Klein (2021b). Miteva, Samwel, and Zabunov (2022) reported for the first time on the association between SEEs 10 (Samwel and Miteva, 2021) and radio emissions. When starting with the list of in situ electrons, the association rate with m-IIs in SC 24 is in the range 12−28%, whereas with DH-IIs is 23−29%.…”
Section: • In Situ Particlesmentioning
confidence: 99%
“…Wind/ WAVES Bougeret et al, 1995) operate near or below these frequencies because they are located well beyond Earth's ionosphere. An instructive table of SRB detectors can be found in Table 1 of Miteva et al (2022). DLITE's primary strength as a SRB detector is its sensitivity.…”
Section: Dlite As An Srb Detectormentioning
confidence: 99%
“…Similar to Type II bursts, these decrease in frequency as the electron beams move through coronal plasma with decreasing background electron densities. The frequency drift rate is much larger than Type II bursts, varying from several MHz s −1 to ≲ 100 MHz s −1 (Reid, 2020;Miteva et al, 2022). The dynamics of Type III bursts can give insights into the evolution of coronal structures like flux tubes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a fascinating and advanced mission would be of great scientific interest to obtain information and solve fundamental physical questions about the formation mechanism of the heliospheric boundary, the nature of the nearby interstellar medium [2], the structure and dynamics of the heliosphere, and the distribution of matter in this part of interplanetary space [3]. Many, if not all, of these issues can only be solved through in situ measurements such as plasma density, ionization state, dust composition and magnetic field strength [4]. However, missions towards (and even beyond) the heliopause region represent a technological challenge [5], as they require the use of advanced propulsion systems [6] to guarantee a cruise velocity of at least 10 au/year if the spacecraft has to be able to reach the desired (very long) distance, greater than 100 au, in a reasonable time interval.…”
Section: Introductionmentioning
confidence: 99%